COVID-19 and livelihoods in rural Guatemala: Lessons from a long term assessment and the path to recovery - Berrospi, Maria Lucia; Ceballos, Francisco; Hernandez, Manuel A.; Paz, Cynthia (International Food Policy Research Institute, 2023)
The COVID-19 pandemic has had profound effects on livelihoods and food security across rural populations worldwide. This study offers a long-term assessment of the impacts of the pandemic and the path to recovery among smallholder agricultural households in the Western Highlands of Guatemala. We rely on a unique longitudinal survey of 1,262 households collected over four survey rounds between 2019 and 2022. The results show substantial recoveries in incomes, food security, and dietary diversity in the region by mid-2022 compared to 2020, but at levels still worse than pre pandemic ones. There is also a sustained increase in the intention to emigrate. The households that were initially more affected in terms of food security and nutrition but recovered faster include those located in one (San Marcos) of the three departments and families living above the poverty line, while smallholders affected by the ETA and IOTA tropical storms, non-coffee producers, and indigenous populations have taken longer to recover. In addition, we provide quantitative estimates for a subsample of households interviewed during a fifth survey round at the end of 2022, showing an average decline of about 16 percent in total household income three years after the start of the pandemic, mainly driven by a decrease in agricultural income, combined with a 26 percent increase in expenditures and an important surge in indebtedness. Overall, the study offers valuable lessons regarding the recovery of vulnerable households following a major global crisis and in a context of additional shocks, remarking the importance of continue monitoring the situation of vulnerable households, especially those exposed to recurrent (weather) shocks that also have a more exhausted portfolio of coping mechanisms & express a higher willingness to emigrate.